Peroral endoscopic myotomy: procedural complications and pain management for the perioperative clinician - Misra L (Dove Medical Press, 2017)
Lopa Misra,1 Norio Fukami,2 Katarina Nikolic,1 Terrence L Trentman1 1Department of Anesthesiology, 2Division of Gastroenterology and Hepatology, Mayo Clinic Arizona, Phoenix, AZ, USA Abstract: Achalasia refers to the lack of smooth muscle relaxation of the distal esophagus. Although nonsurgical treatments such as pneumatic dilatation of the distal esophagus and botulinum toxin injections have been performed, these procedures have limited duration. Similarly, surgical treatment with Heller myotomy is associated with complications. At our institution, we perform the peroral endoscopic myotomy (POEM) in qualified patients. Briefly, POEM involves endoscopic creation of a mid-esophageal submucosal bleb, creation of a submucosal tunnel with the endoscope, and then a distal myotomy, resulting in relaxation of the distal esophagus. The aim of our study is to document perioperative pain and associated pain management for our initial patients undergoing POEM and to review the literature for perioperative complications of this procedure. Therefore, anesthetic and pain management for our initial eleven patients undergoing POEM were reviewed. Patient demographics, pre-POEM pain medication history, perioperative pain medication requirements, and post-POEM pain scores were examined. We found post-POEM pain was usually in the mild–moderate range; a combination of medications was effective (opioids, nonsteroidal anti-inflammatory drugs, acetaminophen). Our literature search revealed a wide frequency range of complications such as pneumoperitoneum and subcutaneous emphysema, with rare serious events such as capnopericardium leading to cardiac arrest. In conclusion, our experience with POEM suggests pain and can be managed adequately with a combination of medications; the procedure appears to be safe and reasonable to perform in an outpatient endoscopy unit. Keywords: pain management, retrospective study, combination of medicines, perioperative, endoscopy